Patients with psychoactive substance use disorders treated in a psychiatric emergency unit - Padilha, Vitoria M.; Santos-Júnior, Amilton dos; Schettini, Carolina S. S.; Azevedo, Renata C. S. (Medicina (Ribeirao Preto), 2016)
Study type: Prevalence study. Objective: To describe the socio demographic and clinical profile of patients with mental and behavioral disorders due to psychoactive substance (PAS) use, evaluated by the Psychiatric team of the Referenced Emergency Unit (REU) at the State University Clinical Hospital of Campinas (UNICAMP-HC). Methods and casuistic: This is a descriptive and quantitative study, which analyzed patients with mental and behavioral disorders due to PAS use, evaluated by the Psychiatric team of the REU-HC-UNICAMP during a period of 12 months, starting on May 2010. Results: There were evaluated 350 patients with PAS related disorders, representing 23.8% of those who sought psychiatric care. Most were males and younger than other patients of the emergency unit. The main reason for seeking help was psychiatric complaint other than PAS related disorders (23.1%), followed by desire to be treated oneself/being admitted to inpatient psychiatric treatment (20.8%) and intoxication (12.5%); 38.5% had a diagnosis of multiple PAS dependence and 34.8% were diagnosed with isolated alcohol dependence; 36% had psychiatric comorbidities and, when compared to other patients, they received more medications during attendance and were less directed to primary care units. Conclusion: There is a high rate of consultations of patients with PAS related problems in the psychiatric emergency unit. Data on the profile of the evaluated these patients can contribute to the improvement of care to this population